Lithium-ion battery failures in consumer electronics - Arora, Ashish; Lele, Sneha Arun; Medora, Noshirwan; Souri, Shukri (Artech House power engineering series., 2019)
Includes technical details of all state-of-the-art Li-on energy storage subsystems and their requirements, this book provides a system designer a single resource detailing all of the common issues navigated when using Li-ion batteries to reduce the risk of field failures. --